Students-generated video assessment for law of conveyancing, Faculty of Law, Universiti Teknologi MARA: a way forward / Noraziah Abu Bakar …[et al.] - Abu Bakar, Noraziah; Ab Hamid, Norliza; Abdullah, Rozlinda; Mansoor, Mazlifah; Mansor, Hariati (UiTM Press, 2021)
Law students at universities are taught substantive and procedural laws to prepare them for legal practice. Thus, during physical class, students’ assessments are dominated by applications of law, giving legal opinions and essay writing. Online assessments during Open and Distance Learning (ODL) require more than just copying and pasting cases, statutory provisions or other materials. In line with the motivation theory, students shall immerse themselves in reading, preparing answers and giving opinion to nurture a comprehensive understanding and interest in substantive and procedural laws. Answering problems posed to them through video production incorporates knowledge, analytical assessment of the issues, and concluding the findings to ensure every aspect of the issues is addressed. The creation of a video requires students to put in time and effort, not just in finding the answer or proposing solutions to the problem, but also requires some technical know-how to produce a suitable video. This paper aims to evaluate whether video assessment during ODL is in line with the theory of motivation that enhanced students’ understanding of the subjects conducted online. A doctrinal method is engaged that reflects a better perception by students through video assessment compared to applications of law through essay writing. Using video creations as a form of assessment encourages law students to develop digital communication skill in order to impart professional legal advice through a creative role-play and enhance their learning of conveyancing law and procedure in a more casual, yet effective, method. To ensure efficacy, the rubric for video assessments shall be clear and precise, and evaluate the contents as well as the presentation skills. Lastly, lecturers as assessors should convey their reflections to students in a comprehensive manner, highlighting their strengths and weaknesses.